Serum α-Klotho associated with oral health among a nationally representative sample of US adults - Chen, Guo-Qiang; Duan, Yao; Wang, Jin-Feng; Lian, Ying; Yin, Xiu-Li (Frontiers in Endocrinology, 2022)
Background: Low klotho is associated with aging-related traits. However, no study has assessed the association between klotho and oral health in large population. This study aimed to explore the association between serum α-klotho and oral health in US Adults. Methods: Data were from the National Health and Nutrition Examination Survey. Oral health parameters included periodontitis, self-rated oral health, and tooth loss. Logistic regression and restricted cubic spline models were adopted to evaluate the associations. Results: A total of 6187 participants were included in the study. The median of the α-klotho level was 815.2 pg/mL. Serum α-Klotho was significantly lower in participants with poor oral health (all P <0.01). Compared with the highest tertile, the lowest tertile of α-klotho was associated with moderate/severe periodontitis, poor-rated oral health, and tooth loss, with OR (95% CI) being 1.21 (1.01, 1.48), 1.26 (1.01, 1.56) and 1.38 (1.05, 1.84), respectively. An increment of per 1 standard deviation in the α-klotho concentration was associated with lower odds of moderate/severe periodontitis (OR: 0.93; 95% CI: 0.87, 0.99). Linear dose-response relationships were found between α-klotho and the odds of moderate/severe periodontitis (P for non-linearity=0.88) and poor-rated oral health (P for non-linearity=0.66). An L-shaped dose-response relationship was found between levels of α-klotho and the odds of tooth loss (P for non-linearity=0.04). Conclusions: Serum α-klotho was associated with oral health. Further studies are necessary to clarify the potential mechanisms and demonstrate the predictive ability of klotho in oral diseases.